Battery assembly based on rectangular silicon wafer and processing method thereof
Through multiple fleece making treatment and surfactant modification, combined with deposition layer optimization, the problems of uneven suede structure and low photoelectric conversion efficiency in rectangular silicon wafer battery modules are solved, and more efficient photoelectric conversion and production efficiency are achieved .
Patent Information
- Application Number
- CN202411302976.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
During the preparation process, existing rectangular silicon wafer battery modules have problems such as uneven corrosion depth, unstable suede structure, uneven film thickness and poor surface morphology, resulting in poor anti-reflection effect of silicon wafers, affecting solar cells. Conversion efficiency and production efficiency.
Three different velvet-making processes are adopted, by adjusting the formula and temperature of the potassium hydroxide solution, controlling the etching rate and depth, combining the modification of the surfactant and the optimization of the deposited layer, a uniform and delicate suede structure is formed, and the low pressure is passed. Diffusing, SE laser, polishing, oxidation and annealing processes improve the photoelectric conversion efficiency of silicon wafers.
The uniformity and consistency of the suede structure of the silicon wafer is achieved, the light absorption efficiency and battery conversion efficiency are improved, and the performance and production efficiency of battery modules are enhanced.
Smart Images

Figure BDA0005048248110000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cell preparation, in particular to a cell assembly based on a rectangular silicon wafer and a processing method thereof. Background Art
[0002] With the continuous growth of global demand for renewable energy, the innovation and development of industry technology, "rectangular silicon wafer cells" have been launched one after another. Components based on rectangular silicon wafer cells can further tap the potential of components in the length direction, make full use of container space, and bring greater value to the industrial chain. In the existing technology, the traditional silicon wafer manufacturing method has problems such as uneven corrosion depth, unstable velvet structure, uneven film thickness, and poor surface morphology due to improper preparation processes such as texturing and deposition anti-reflection. These factors will lead to poor anti-reflection effect of silicon wafers, affect the conversion efficiency of solar cells, and limit the flexibility and production efficiency of the production line.
[0003] In summary, it is of great significance to prepare a battery component based on rectangular silicon wafers. Summary of the invention
[0004] The object of the present invention is to provide a battery assembly based on a rectangular silicon wafer and a processing method thereof to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for processing a battery assembly based on a rectangular silicon wafer comprises the following steps:
[0007] Step 1: (1) placing a single crystal silicon wafer in a potassium hydroxide solution, performing texturing treatment, washing, and drying to obtain a texturing silicon wafer; (2) subjecting the texturing silicon wafer to low-pressure diffusion, SE laser, polishing, and oxidation annealing in sequence to obtain a silicon wafer A;
[0008] Step 2: depositing an aluminum oxide layer and a silicon nitride layer on the back of silicon wafer A in sequence to obtain silicon wafer B;
[0009] Step 3: depositing a silicon nitride layer on the front surface of silicon wafer B to obtain a rectangular silicon wafer;
[0010] Step 4: (1) Laser grooving, screen printing, and sintering are performed on rectangular silicon wafers to obtain single cell sheets; (2) The single cell sheets are connected in series using welding ribbons to obtain cell strings; (3) After laying glass, POE / EPE, cell strings, EVA, and grid-glazed backplane glass in sequence, the edges are sealed with an edge-sealing tape machine and then flow into the next process of lamination, framing, and installing a junction box to obtain a rectangular silicon wafer cell assembly.
[0011] More optimally, the size of the monocrystalline silicon wafer is 180-185×205-215 mm2 .
[0012] More optimally, the texturing process is specifically as follows: adding the single crystal silicon wafer to potassium hydroxide solution A, soaking it at 60-75°C for 10-15 minutes, washing it with water, and drying it to obtain a primary texturing single crystal silicon wafer; adding the primary texturing single crystal silicon wafer to potassium hydroxide solution B again, soaking it at 75-85°C for 20-25 minutes, washing it with water, and drying it to obtain a secondary texturing single crystal silicon wafer; adding the secondary texturing single crystal silicon wafer to potassium hydroxide solution C again, soaking it at 70-80°C for 15-20 minutes, washing it with water, and drying it to obtain a texturing silicon wafer.
[0013] More optimally, the potassium hydroxide solution A comprises the following components: 1.5wt% to 2wt% KOH, 0.04wt% to 0.06wt% boric acid, 0.04wt% to 0.05wt% amino acid, 1wt% to 2wt% isopropanol, 4wt% to 5wt% ethanol, and the rest is deionized water;
[0014] The potassium hydroxide solution B comprises the following components: 1.5wt% to 2wt% KOH, 0.2wt% to 0.3wt% surfactant, 0.04wt% to 0.06wt% boric acid, 1wt% to 2wt% isopropanol, 4wt% to 5wt% ethanol, and the rest is deionized water;
[0015] The potassium hydroxide solution C comprises the following components: 1.5 wt% to 2 wt% KOH, 0.1 wt% to 0.2 wt% surfactant, 0.04 wt% to 0.06 wt% amino acid, 1 wt% to 2 wt% isopropanol, 4 wt% to 5 wt% ethanol, and the rest is deionized water.
[0016] Among them, boric acid is added as a corrosion inhibitor in the potassium hydroxide solution A during the first texturing process to control the etching rate, make the etching process more uniform, and avoid surface unevenness caused by excessive etching; amino acids are used as auxiliary additives to help improve the microscopic morphology of the etched surface and promote the formation of a more uniform velvet surface; a rough velvet structure is initially formed, laying the foundation for subsequent processing.
[0017] In a further scheme, a surfactant is added to the potassium hydroxide solution B during the secondary texturing process to increase the wettability and permeability of the solution, making the etching more uniform and deep, which helps to form a more complex velvet structure and improve the light capture capability. In addition, boric acid is added to the secondary texturing process to effectively control the etching rate of potassium hydroxide (KOH) on the silicon wafer surface. As boric acid continuously releases more hydroxyl groups, its wetting effect on the silicon wafer is significantly enhanced, resulting in the pyramid structure on the silicon wafer surface being gradually smoothed and polished, thereby promoting a gradual increase in reflectivity, making the etching process more uniform, and avoiding surface unevenness caused by excessive etching. The presence of boric acid promotes the formation of a more complex velvet structure on the silicon wafer surface, which helps to increase the light absorption area and reduce light reflection, thereby improving the photoelectric conversion efficiency. Boric acid is more acidic than amino acids, and a larger amount of surfactant is added.
[0018] In a further solution, a small amount of surfactant was added to the potassium hydroxide solution C during the three-time texturing soaking. This is because amino acids are added. Compared with boric acid, amino acids are weak acids. The addition of a small amount of surfactant fine-tunes the surface roughness to avoid excessive etching. The addition of amino acids helps to further refine the microstructure of the silicon wafer surface, making the velvet surface more uniform and delicate. This optimization of the microstructure helps to improve the light capture ability and thus improve the photoelectric conversion efficiency.
[0019] More optimally, the preparation method of the surfactant is:
[0020] Step 1: Add polyethylene glycol monomethyl ether to DMF and disperse evenly to obtain solution A; add lutidine and methanesulfonic anhydride in sequence, stir and react at 65-75° C. for 12-14 hours, evaporate the solvent, and obtain sulfonate;
[0021] Step 2: Add lignin to deionized water and stir evenly, add potassium hydroxide to adjust the pH to 11±0.2; add sodium vinyl sulfonate and sulfonate, stir and react at 65-75° C. for 12-14 hours, purify, and obtain modified lignin;
[0022] Step 3: Add the modified lignin, cysteine and azobisisobutyronitrile to tetrahydrofuran, stir evenly, stir and react for 3 to 4 hours under ultraviolet light, wash and dry to obtain a surfactant.
[0023] More optimally, the raw materials of the sulfonate include the following raw materials by weight: 4 to 5 parts of polyethylene glycol monomethyl ether, 40 to 45 parts of DMF, 0.3 to 0.5 parts of lutidine, and 3.5 to 4 parts of methanesulfonic anhydride;
[0024] The raw materials of the modified lignin include the following raw materials by weight: 9 to 11 parts of lignin, 7 to 9 parts of sodium vinyl sulfonate, 2 to 3 parts of sulfonate, and 45 to 55 parts of deionized water;
[0025] The raw materials of the surfactant include the following raw materials in parts by weight: 7 to 8 parts of cysteine, 0.3 to 0.5 parts of azobisisobutyronitrile, 8 to 9 parts of modified lignin, and 40 to 45 parts of tetrahydrofuran.
[0026] Among them, the low molecular weight polyethylene glycol monomethyl ether reacts with the sulfonic acid group in methanesulfonic anhydride under the alkaline catalyst of dimethylpyridine to produce a sulfonate with a sulfonic acid group; the multiple hydroxyl groups in lignin react with the sulfonic acid group and sodium vinyl sulfonate under the alkaline catalyst of potassium hydroxide again to undergo a sulfonation reaction, and multiple vinyl groups are grafted; the grafted vinyl groups react with the thiol groups in cysteine to undergo free radical polymerization under the initiator of azobisisobutyronitrile to form a surfactant with a special structure and properties. Cysteine and the above amino acids produce a synergistic effect, which can reduce the surface tension of water, enhance the wetting, penetration, emulsification, dispersion and solubilization capabilities of the solution, and further enhance the effectiveness of the surfactant; the prepared surfactant has excellent surface activity, can significantly reduce the surface tension of water, and improve the wettability and permeability of potassium hydroxide solution. This helps to cover the surface of the silicon wafer more evenly during the texturing process and improve the etching effect; the surfactant can enhance the wettability of the silicon wafer by reducing the surface tension of the liquid surface, thereby improving the efficiency of cleaning and processing. When adsorbed on the surface of silicon wafer, this substance can effectively weaken OH - The direct contact between the ions and the silicon wafer surface slows down the rate of chemical reactions, helps control the reaction process, and prevents excessive reactions from adversely affecting the silicon wafer.
[0027] More optimally, the polishing process is as follows: immerse the SE laser-textured silicon wafer in an alkaline solution at 60°C to 75°C for 120 to 150 seconds, pickle with 70wt% to 75wt% nitric acid at room temperature for 4 to 5 minutes, wash with water, and dry;
[0028] The alkali solution comprises anhydrous ethanol, sodium hydroxide and deionized water in a mass ratio of 0.5-1:2-3:60.
[0029] More optimally, the silicon wafer A is deposited on the back side by reactive magnetron sputtering to obtain an aluminum oxide layer with a thickness of 2 to 15 nm and a silicon nitride layer with a thickness of 40 to 110 nm;
[0030] The silicon wafer B is deposited on the front surface of the silicon wafer B by chemical vapor deposition to obtain a silicon nitride layer with a thickness of 60 to 80 nm.
[0031] Among them, an aluminum oxide layer with a thickness of 2 to 15 nm and a silicon nitride layer with a thickness of 40 to 110 nm are deposited on the back side by reactive magnetron sputtering, which produces a passivation effect and can effectively reduce the interface state density and reduce the surface recombination rate, thereby improving the open circuit voltage and conversion efficiency of the battery; the silicon nitride layer can reflect more unabsorbed long-wavelength photons back to the interior of the battery for secondary absorption, thereby improving the short-circuit current density and conversion efficiency of the battery.
[0032] In a further solution, a 60-80nm thick silicon nitride layer is deposited on the front surface by chemical vapor deposition to play an anti-reflection role. By adjusting the thickness and refractive index of the silicon nitride layer, low reflectivity can be achieved in a wide spectral range, thereby improving the solar absorption efficiency of the battery; at the same time, a passivation effect is also produced, which can also improve the open circuit voltage and fill factor of the battery to a certain extent.
[0033] More optimally, the low-pressure diffusion temperature is 700-1000°C; the oxidation annealing temperature is 650-800°C, and the time is 5-10 minutes; and the sintering temperature is 600-1000°C.
[0034] More optimally, a rectangular silicon wafer battery assembly is prepared by a processing method of a rectangular silicon wafer-based battery assembly.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The scheme uses three different texturing processes to gradually refine the texture structure. By adjusting the formula of potassium hydroxide solution, texturing temperature, and texturing time, the etching rate and depth can be precisely controlled, which helps to ensure the uniformity and consistency of the texture structure, thereby enhancing the performance of the silicon wafer;
[0037] 2. The surfactant prepared in the scheme can improve the surface activity through multiple modifications and grafting, which helps to more evenly cover the surface of the silicon wafer during the texturing process, improve the texturing effect, and thus help to improve the light absorption efficiency and photoelectric conversion efficiency of the silicon wafer;
[0038] 3. The scheme produces a passivation effect by controlling the thickness of the aluminum oxide layer and the silicon nitride layer deposited on the back side and the thickness of the silicon nitride layer deposited on the front side, thereby reducing the interface state density and the surface recombination rate, thereby improving the open circuit voltage and conversion efficiency of the battery. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] It should be noted that the following parts are by mass, and the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and are exemplified as follows: in the following embodiments, the purity of POE is 99%, and the CAS number is 68441-17-8; the EVA model is UE647-04, purchased from Dongguan Yingxiang Plastic Raw Materials Co., Ltd.; polyethylene glycol monomethyl ether is polyethylene glycol monomethyl ether 200, the product number is P30442, purchased from Shenzhen Feisi Biotechnology Co., Ltd.
[0041] In the following scheme, the specifications of the monocrystalline silicon wafer are specifically 182.2×210mm 2 ;
[0042] The preparation method of the surfactant is as follows: (1) adding 4.5 parts of polyethylene glycol monomethyl ether to 43 parts of DMF and dispersing them uniformly to obtain solution A; adding 0.4 parts of lutidine and 3.7 parts of methanesulfonic anhydride in sequence, stirring and reacting at 70°C for 12 hours, evaporating the solvent, and obtaining sulfonate; (2) adding 10 parts of lignin to 50 parts of deionized water and stirring them uniformly, adding potassium hydroxide to adjust the pH to 11.1; adding 8 parts of sodium vinyl sulfonate and 2.5 parts of sulfonate, stirring and reacting at 70°C for 13 hours, purifying, and obtaining modified lignin; (3) adding 8.5 parts of modified lignin, 7.5 parts of cysteine, and 0.4 parts of azobisisobutyronitrile to 42 parts of tetrahydrofuran, stirring them uniformly, stirring and reacting under ultraviolet light for 3.5 hours, washing and drying, and obtaining a surfactant;
[0043] Potassium hydroxide solution A comprises the following components: 1.8 wt% KOH, 0.05 wt% boric acid, 0.045 wt% amino acid, 1.5 wt% isopropanol, 4.5 wt% ethanol, and the rest is deionized water;
[0044] Potassium hydroxide solution B includes the following components: 1.8wt% KOH, 0.25wt% surfactant, 0.05wt% boric acid, 1.5wt% isopropanol, 4.5% ethanol, and the rest is deionized water;
[0045] Potassium hydroxide solution C includes the following components: 1.8 wt % KOH, 0.15 wt % surfactant, 0.05 wt % amino acid, 1.5 wt % isopropanol, 4.5 wt % ethanol, and the rest is deionized water.
[0046] Embodiment 1: A method for processing a battery assembly based on a rectangular silicon wafer, comprising the following steps:
[0047] Step 1: Add the single crystal silicon wafer into potassium hydroxide solution A (flat, mass ratio of 1:20), soak at 65°C for 12 minutes, wash with water, and dry to obtain a single crystal silicon wafer with primary texturing; add the single crystal silicon wafer with primary texturing again into potassium hydroxide solution B (flat, mass ratio of 1:20), soak at 80°C for 22 minutes, wash with water, and dry to obtain a single crystal silicon wafer with secondary texturing; add the single crystal silicon wafer with secondary texturing again into potassium hydroxide solution C (flat, mass ratio of 1:20), soak at 75°C for 17 minutes, wash with water, and dry to obtain a texturing silicon wafer;
[0048] Step 2: The textured silicon wafer was diffused at low pressure at 850°C, treated with SE laser, and polished in alkaline solution (the mass ratio of anhydrous ethanol, sodium hydroxide, and deionized water is 0.8:2.5:60) at 68°C for 130s, pickled with 72wt% nitric acid at room temperature for 4.5 minutes, washed with water, dried, and oxidized annealed at 730°C for 7 minutes to obtain silicon wafer A;
[0049] Step 3: (1) depositing an aluminum oxide layer with a thickness of 10 nm and a silicon nitride layer with a thickness of 75 nm on the back surface of silicon wafer A to obtain silicon wafer B; (2) depositing a silicon nitride layer with a thickness of 70 nm on the front surface of silicon wafer B to obtain a rectangular silicon wafer;
[0050] Step 4: (1) Laser grooving, screen printing, and sintering at 800°C are performed on rectangular silicon wafers to obtain single cell sheets; (2) The single cell sheets are connected in series using welding ribbons to obtain cell strings; (3) After laying glass, POE / EPE, cell strings, EVA, and grid-glazed backplane glass in sequence, the edges are sealed with an edge-sealing tape machine and then flow into the next process of lamination, framing, and installing a junction box to obtain a rectangular silicon wafer cell assembly.
[0051] Embodiment 2: A method for processing a battery assembly based on a rectangular silicon wafer, comprising the following steps:
[0052] Step 1: Add the single crystal silicon wafer into potassium hydroxide solution A (flat, mass ratio of 1:20), soak at 65°C for 10 minutes, wash with water, and dry to obtain a single crystal silicon wafer with primary texturing; add the single crystal silicon wafer with primary texturing again into potassium hydroxide solution B (flat, mass ratio of 1:20), soak at 80°C for 20 minutes, wash with water, and dry to obtain a single crystal silicon wafer with secondary texturing; add the single crystal silicon wafer with secondary texturing again into potassium hydroxide solution C (flat, mass ratio of 1:20), soak at 75°C for 15 minutes, wash with water, and dry to obtain a texturing silicon wafer;
[0053] Step 2: The textured silicon wafer is subjected to low-pressure diffusion at 700°C, SE laser, and the textured silicon wafer after SE laser is immersed in an alkaline solution (the mass ratio of anhydrous ethanol, sodium hydroxide, and deionized water is 0.8:2.5:60) at 60°C and polished for 130s, pickled with 72wt% nitric acid at room temperature for 4.5 minutes, washed with water, dried, and oxidized annealed at 650°C for 5 minutes to obtain silicon wafer A;
[0054] Step 3: (1) depositing an aluminum oxide layer with a thickness of 2 nm and a silicon nitride layer with a thickness of 40 nm on the back surface of silicon wafer A to obtain silicon wafer B; (2) depositing a silicon nitride layer with a thickness of 60 nm on the front surface of silicon wafer B to obtain a rectangular silicon wafer;
[0055] Step 4: (1) Laser grooving, screen printing, and sintering at 600°C are performed on rectangular silicon wafers to obtain single cell sheets; (2) The single cell sheets are connected in series using welding ribbons to obtain cell strings; (3) After laying glass, POE / EPE, cell strings, EVA, and grid-glazed backplane glass in sequence, the edges are sealed with an edge-sealing tape machine and then flow into the next process of lamination, framing, and installing a junction box to obtain a rectangular silicon wafer cell assembly.
[0056] Embodiment 3: A method for processing a battery assembly based on a rectangular silicon wafer, comprising the following steps:
[0057] Step 1: Add the single crystal silicon wafer into potassium hydroxide solution A (flat, mass ratio of 1:20), soak at 65°C for 15 minutes, wash with water, and dry to obtain a single crystal silicon wafer with primary texturing; add the single crystal silicon wafer with primary texturing again into potassium hydroxide solution B (flat, mass ratio of 1:20), soak at 80°C for 25 minutes, wash with water, and dry to obtain a single crystal silicon wafer with secondary texturing; add the single crystal silicon wafer with secondary texturing again into potassium hydroxide solution C (flat, mass ratio of 1:20), soak at 75°C for 20 minutes, wash with water, and dry to obtain a texturing silicon wafer;
[0058] Step 2: The textured silicon wafer is subjected to low-pressure diffusion at 1000°C, SE laser, and the textured silicon wafer after SE laser is immersed in an alkaline solution (the mass ratio of anhydrous ethanol, sodium hydroxide, and deionized water is 0.8:2.5:60) at 75°C and polished for 130s, pickled with 72wt% nitric acid at room temperature for 4.5 minutes, washed with water, dried, and oxidized annealed at 800°C for 10 minutes to obtain silicon wafer A;
[0059] Step 3: (1) depositing an aluminum oxide layer with a thickness of 15 nm and a silicon nitride layer with a thickness of 110 nm on the back surface of silicon wafer A to obtain silicon wafer B; (2) depositing a silicon nitride layer with a thickness of 80 nm on the front surface of silicon wafer B to obtain a rectangular silicon wafer;
[0060] Step 4: (1) Laser grooving, screen printing, and sintering at 1000°C are performed on rectangular silicon wafers to obtain single cell sheets; (2) The single cell sheets are connected in series using welding ribbons to obtain cell strings; (3) After laying glass, POE / EPE, cell strings, EVA, and grid-glazed backplane glass in sequence, the edges are sealed with an edge-sealing tape machine and then flow into the next process of lamination, framing, and installing a junction box to obtain a rectangular silicon wafer cell assembly.
[0061] Comparative Example 1: Based on Example 1, in the texturing process, only one treatment is performed, and the other processes remain unchanged, specifically:
[0062] Step 1: Soak the single crystal silicon wafer in potassium hydroxide solution B at 80°C for 55 minutes (flat, mass ratio of 1:20), wash with water, and dry to obtain a texturing silicon wafer.
[0063] Comparative Example 2: Based on Example 1, the surfactant was changed to 0.2 wt% PEG 400, and the other processes remained unchanged, specifically:
[0064] Potassium hydroxide solution A comprises the following components: 1.8 wt% KOH, 0.05 wt% boric acid, 0.045 wt% amino acid, 1.5 wt% isopropanol, 4.5 wt% ethanol, and the rest is deionized water;
[0065] Potassium hydroxide solution B includes the following components: 1.8 wt% KOH, 0.2 wt% PEG 400, 0.05 wt% boric acid, 1.5 wt% isopropanol, 4.5% ethanol, and the rest is deionized water;
[0066] Potassium hydroxide solution C includes the following components: 1.8 wt% KOH, 0.2 wt% PEG 400, 0.05 wt% amino acid, 1.5 wt% isopropanol, 4.5 wt% ethanol, and the rest is deionized water.
[0067] Comparative Example 3: Based on Example 1, the same solution was used three times in the texturing process, and the other processes remained unchanged, specifically:
[0068] Step 1: Add the single crystal silicon wafer into potassium hydroxide solution B (flat, mass ratio of 1:20), soak it at 65℃ for 15min, wash it with water, and dry it to obtain a single crystal silicon wafer with primary texturing; add the single crystal silicon wafer with primary texturing into potassium hydroxide solution B again (flat, mass ratio of 1:20), soak it at 80℃ for 25min, wash it with water, and dry it to obtain a single crystal silicon wafer with secondary texturing; add the single crystal silicon wafer with secondary texturing into potassium hydroxide solution B again (flat, mass ratio of 1:20), soak it at 75℃ for 20min, wash it with water, and dry it to obtain a texturing silicon wafer.
[0069] Comparative Example 4: Based on Example 1, the thickness of the aluminum oxide layer and the silicon nitride layer in the back deposition was changed, and the other processes remained unchanged, specifically:
[0070] Step 3: (1) Deposit an aluminum oxide layer with a thickness of 10 nm and a silicon nitride layer with a thickness of 75 nm on the back side of silicon wafer A to obtain silicon wafer B; (2) Deposit a silicon nitride layer with a thickness of 70 nm on the front side of silicon wafer B to obtain a rectangular silicon wafer.
[0071] Test experiment: The performance of a battery assembly based on a rectangular silicon wafer prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested: (1) Reflectivity test: The silicon wafers prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested with a wavelength range of 600 nm and a wavelength interval of 1 nm according to the electronic industry standard "SJ / T 11760-2020"; (2) Conversion efficiency test: The battery assembly prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested with a temperature of 25°C and a light irradiance of 1000 W / m2 according to the national standard "GB / T 39857-2021". 2 Test it below.
[0072]
[0073] Table 1
[0074] Result analysis: According to the data analysis in Table 1, it can be seen that the present invention prepares surfactants through grafting modification to improve surface activity, which helps to improve the texturing effect and improve the light absorption efficiency and photoelectric conversion efficiency of silicon wafers; through three texturing treatments at different temperatures, different times, and different ratios of potassium hydroxide solutions, it directly affects the formation of the pyramid structure, helps to avoid over-etching or under-etching, ensures the uniformity and consistency of the velvet structure, and thus enhances the performance of the silicon wafer; in addition, by controlling the thickness of the aluminum oxide layer and the silicon nitride layer in the back deposition and the thickness of the silicon nitride layer deposited on the front, it directly affects the recombination rate of the silicon wafer surface, produces interface characteristics, and improves conversion efficiency and stability.
[0075] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for processing a battery assembly based on a rectangular silicon wafer, characterized in that: The following steps are involved: Step 1: (1) placing a single crystal silicon wafer in a potassium hydroxide solution, performing texturing treatment, washing, and drying to obtain a texturing silicon wafer; (2) subjecting the texturing silicon wafer to low-pressure diffusion, SE laser, polishing, and oxidation annealing in sequence to obtain a silicon wafer A; Step 2: depositing an aluminum oxide layer and a silicon nitride layer on the back of silicon wafer A in sequence to obtain silicon wafer B; Step 3: depositing a silicon nitride layer on the front surface of silicon wafer B to obtain a rectangular silicon wafer; Step 4: (1) laser grooving, screen printing, and sintering are performed on a rectangular silicon wafer to obtain a single cell; (2) Single cells are connected in series using welding ribbons to obtain a cell string; (3) After laying glass, POE / EPE, cell string, EVA, and grid-glazed backplane glass in sequence, the edges are sealed with an edge-sealing tape machine and then flow into the next process of lamination, framing, and installing a junction box to obtain a rectangular silicon wafer cell assembly.
2. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 1, characterized in that: The specifications of the single crystal silicon wafer are 180-185×205-215mm 2 .
3. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 1, characterized in that: The specific process of the texturing treatment is as follows: adding a single crystal silicon wafer to a potassium hydroxide solution A, soaking it at 60-75°C for 10-15 minutes, washing it with water, and drying it to obtain a single crystal silicon wafer with a primary texturing; adding the single crystal silicon wafer with a primary texturing again to a potassium hydroxide solution B, soaking it at 75-85°C for 20-25 minutes, washing it with water, and drying it to obtain a single crystal silicon wafer with a secondary texturing; adding the single crystal silicon wafer with a secondary texturing again to a potassium hydroxide solution C, soaking it at 70-80°C for 15-20 minutes, washing it with water, and drying it to obtain a texturing silicon wafer.
4. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 3, characterized in that: The potassium hydroxide solution A comprises the following components: 1.5wt% to 2wt% KOH, 0.04wt% to 0.06wt% boric acid, 0.04wt% to 0.05wt% amino acid, 1wt% to 2wt% isopropanol, 4wt% to 5wt% ethanol, and the rest is deionized water; The potassium hydroxide solution B comprises the following components: 1.5wt% to 2wt% KOH, 0.2wt% to 0.3wt% surfactant, 0.04wt% to 0.06wt% boric acid, 1wt% to 2wt% isopropanol, 4wt% to 5wt% ethanol, and the rest is deionized water; The potassium hydroxide solution C comprises the following components: 1.5 wt% to 2 wt% KOH, 0.1 wt% to 0.2 wt% surfactant, 0.04 wt% to 0.06 wt% amino acid, 1 wt% to 2 wt% isopropanol, 4 wt% to 5 wt% ethanol, and the rest is deionized water.
5. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 4, characterized in that: The preparation method of the surfactant is: Step 1: Add polyethylene glycol monomethyl ether to DMF and disperse evenly to obtain solution A; add lutidine and methanesulfonic anhydride in sequence, stir and react at 65-75° C. for 12-14 hours, evaporate the solvent, and obtain sulfonate; Step 2: Add lignin to deionized water and stir evenly, add potassium hydroxide to adjust the pH to 11±0.2; add sodium vinyl sulfonate and sulfonate, stir and react at 65-75° C. for 12-14 hours, purify, and obtain modified lignin; Step 3: Add the modified lignin, cysteine and azobisisobutyronitrile to tetrahydrofuran, stir evenly, stir and react for 3 to 4 hours under ultraviolet light, wash and dry to obtain a surfactant.
6. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 5, characterized in that: The raw materials of the sulfonate ester include the following raw materials by weight: 4 to 5 parts of polyethylene glycol monomethyl ether, 40 to 45 parts of DMF, 0.3 to 0.5 parts of lutidine, and 3.5 to 4 parts of methanesulfonic anhydride; The raw materials of the modified lignin include the following raw materials by weight: 9 to 11 parts of lignin, 7 to 9 parts of sodium vinyl sulfonate, 2 to 3 parts of sulfonate, and 45 to 55 parts of deionized water; The raw materials of the surfactant include the following raw materials in parts by weight: 7 to 8 parts of cysteine, 0.3 to 0.5 parts of azobisisobutyronitrile, 8 to 9 parts of modified lignin, and 40 to 45 parts of tetrahydrofuran.
7. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 1, characterized in that: The polishing process is specifically as follows: immersing the SE laser-textured silicon wafer in an alkaline solution at 60° C. to 75° C. for 120 to 150 seconds, pickling with 70wt% to 75wt% nitric acid at room temperature for 4 to 5 minutes, washing with water, and drying; The alkali solution comprises anhydrous ethanol, sodium hydroxide and deionized water in a mass ratio of 0.5-1:2-3:
60.
8. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 1, characterized in that: The silicon wafer A is subjected to reactive magnetron sputtering to deposit an aluminum oxide layer with a thickness of 2 to 15 nm and a silicon nitride layer with a thickness of 40 to 110 nm on the back side; The silicon wafer B is deposited on the front surface of the silicon wafer B by chemical vapor deposition to obtain a silicon nitride layer with a thickness of 60 to 80 nm.
9. The method for processing a battery assembly based on a rectangular silicon wafer according to claim 1, characterized in that: The low-pressure diffusion temperature is 700-1000°C; the oxidation annealing temperature is 650-800°C, and the time is 5-10 minutes; and the sintering temperature is 600-1000°C.
10. A rectangular silicon wafer battery assembly prepared according to the method for processing a rectangular silicon wafer-based battery assembly according to any one of claims 1 to 9.
Citation Information
Cited By
Photovoltaic cell, preparation method thereof, photovoltaic module and photovoltaic system
CN122054760A